2020
DOI: 10.3389/fpsyg.2020.01812
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 Confinement in Behavioral, Psychological, and Training Patterns of Chess Players

Abstract: The outbreak of COVID-19 has triggered a pandemic, jeopardizing global health. The sports world is also suffering enormous consequences, such as the suspension of the Olympic Games in Tokyo or, in chess, the cancelation of the World Candidates Tournament 2020. Chess is a sport characterized by high psychophysiological demands derived from long training durations, tournaments, and games, leading to mental, emotional, and physical stress. These characteristics could provide chess players a certain advantage in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
5
35
0
Order By: Relevance
“…Authors attributed these phenomena to the larger experience of high-performance athletes in coping with competition-related anxiety and the higher cognitive resources professional athletes have. Similar results were observed in professional chess players by Fuentes-García et al ( 49 ) despite the decrease of physical activity, which suggests that the cognitive resources of athletes potentially mitigate the negative effects of confinement. However, the same studies previously mentioned showed contradictory results in terms of academic levels and subjective perception of the confinement situation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Authors attributed these phenomena to the larger experience of high-performance athletes in coping with competition-related anxiety and the higher cognitive resources professional athletes have. Similar results were observed in professional chess players by Fuentes-García et al ( 49 ) despite the decrease of physical activity, which suggests that the cognitive resources of athletes potentially mitigate the negative effects of confinement. However, the same studies previously mentioned showed contradictory results in terms of academic levels and subjective perception of the confinement situation.…”
Section: Discussionsupporting
confidence: 85%
“…However, the same studies previously mentioned showed contradictory results in terms of academic levels and subjective perception of the confinement situation. On the one hand, chess players with university studies showed greater concern about the COVID-19 pandemic ( 49 ), while Olympic athletes with higher education showed more dissatisfaction with the confinement measures as a result of the COVID-19 pandemic ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 home confinement increased the level of sedentarism among the general population (Fuentes-García et al, 2020 ; Narici et al, 2020 ). This, linked to a high uncertainty and stress (Lin et al, 2020 ), led to a significant decrease in the psychological health (Ammar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides its social, psychological, and economic impact, COVID-19 has affected sports activities too, with major competitions and events being canceled/postponed (Fuentes-García et al, 2020;Guerrero-Calderón, 2020). Also, professional soccer has been affected (Guerrero-Calderón, 2020).…”
Section: Introductionmentioning
confidence: 99%